Step * 1 1 1 2 of Lemma rmul-distrib1


1. : ℝ
2. : ℝ
3. : ℝ
⊢ bdd-diff(λ2n.(x z) n;λ2n.reg-seq-mul(x;z) n)
BY
((Assert bdd-diff(x z;reg-seq-mul(x;z)) BY Auto)⋅ THEN NthHypEq (-1) THEN EqCD THEN Auto)⋅ }


Latex:


Latex:

1.  x  :  \mBbbR{}
2.  y  :  \mBbbR{}
3.  z  :  \mBbbR{}
\mvdash{}  bdd-diff(\mlambda{}\msubtwo{}n.(x  *  z)  n;\mlambda{}\msubtwo{}n.reg-seq-mul(x;z)  n)


By


Latex:
((Assert  bdd-diff(x  *  z;reg-seq-mul(x;z))  BY  Auto)\mcdot{}  THEN  NthHypEq  (-1)  THEN  EqCD  THEN  Auto)\mcdot{}




Home Index